The multidimensional well-being of Asian senior citizens: A systematic review - Dil Bahadur Rahut; Alessia Destefanis (Asian Development Bank Institute (ADBI), 2024)
Since the 1960s, global societies have experienced a decline in both fertility and mortality rates; this trend has led to rapidly aging populations worldwide. In such a scenario, aging populations have become a significant challenge, especially for developing Asian economies where both healthcare and pension systems still need to be properly shaped. Thus, this paper aims to provide an up-to-date systematic review of the empirical and theoretical literature on the well-being of elderly people in developing Asia. First, we analyze the current framework, and we provide a definition for the concept of multidimensional well-being. Then, we discuss the main relevant empirical and theoretical outcomes from the literature, focusing on those related to the three main dimensions of well-being (i.e., socioeconomic, mental, and physical). Furthermore, we highlight the current barriers and the future challenges that policymakers in aging economies will face. Finally, we suggest priorities for policy initiatives in developing Asia, and we emphasize areas of future research.
Keywords: I14; I15; I31; J14; O53; 330; aging; developing Asia; well-being; mental; socioeconomic; physical